A review: Progress and perspectives of research on the functionalities of phase change materials. (October 2022) - Xu, Jiayi; Zhang, Xuelai; Zou, Lingen
Abstract: With the widespread attention of the phase change materials (PCMs) due to its excellent energy storage effects, the functional requirements of PCMs are becoming more and more demanding. Considering the problems of solid-liquid transition leakage and rigid-contact thermal resistance, this paper mainly summarizes the specific methods to solve this problem based on the research on the form stability and flexibility of PCMs in recent years. As well as, a brief review of the electrical conductivity and flame retardant properties has also been presented. The analysis shows that capillary force is an important indicator of leakage prevention, and that chemical flexibility has better stability. Also, flame retardancy is essential in highly thermally conductive materials, while electrical conductivity is chosen according to the demand. The challenges in future research process are also pointed out, providing a reference for subsequent research of some significance. Highlights: First integration of research progress on the functionality of phase change materials The concept of using one additive to replace more is introduced. The results of this paper can guide the practical PCMs optimization.